THE IMPORTANCE OF MULTIDISCIPLINARY HEALTH TEAMS IN INDIGENOUS AREAS - da Silva Rodrigues Filho, Pedro (Health and Society, 2021)
Introduction: The importance of multidisciplinary health teams in indigenous areas can be understood as a major advance in the actions of public health, maintained by the Ministry of Health, mainly after the implementation of the Auroca Law to SUS. Objective: To address the importance of multidisciplinary teams in indigenous health. Methodology: This is a descriptive method of using revision methods. Literature Latin American Literature in Health Sciences (LILACS). FINAL CONSIDERATIONS: There has been great progress in the care provided by SUS to indigenous communities in recent years. But the biggest problem faced by the health teams is the lack of equipment needed to carry out adequate treatment, shortage of human resources, in addition to the demographic issue, where many villages are difficult to access for health teams.